Cortisol and pregnancy-related anxiety in relation to preeclampsia among third-trimester pregnant women: A case–control study from Aceh, Indonesia - Hezron, Teuku M.; Dewi, Tgk. Puspa; Septivera, Yusra; Rajuddin, Rajuddin; Utami, Niken A. (Narra Sains Indonesia, 2025)
Despite extensive research, the interplay between hormonal stress markers and pregnancy-specific anxiety in the pathogenesis of preeclampsia remains insufficiently understood. This study aimed to analyze the simultaneous relationships between serum cortisol levels, pregnancy-related anxiety, and the occurrence of preeclampsia among third-trimester pregnant women. A case–control study was conducted at three hospitals in Banda Aceh, Indonesia, involving third-trimester pregnant women. Serum cortisol concentrations were measured using an immunoassay, and anxiety levels were assessed with the validated Pregnancy Related Anxiety Questionnaire (PRAQ). Preeclampsia diagnosis followed standard clinical and laboratory criteria. Associations between cortisol levels (categorized into high and normal) and PRAQ scores (classified as high and low–moderate) with preeclampsia were evaluated using the Chi-squared test, and crude odds ratios (OR) with 95% confidence intervals (95%CI). The Spearman’s correlation was used to determine the correlation between cortisol levels and PRAG scores. A total of 66 pregnant women were included in the final analysis (33 with preeclampsia and 33 with normal pregnancy). Women with high serum cortisol levels had a markedly greater likelihood of developing preeclampsia compared with those with normal cortisol levels (odds ratio (OR)=34.00; 95% confidence interval (95%CI): 4.93–234.46). Similarly, women with high pregnancy-related anxiety exhibited a significantly elevated risk of preeclampsia (OR=16.71; 95%CI: 4.95–56.39). No significant correlation was observed between cortisol levels and PRAQ scores in both groups (preeclampsia: r=-0.041, p=0.821; normal pregnancy: r=0.278, p=0.117). In conclusion, elevated serum cortisol and high pregnancy-related anxiety are independently associated with preeclampsia, although not directly correlated with each other. These findings highlight the potential of dual screening for cortisol and pregnancy-specific anxiety as an innovative approach for early identification of women at high risk of preeclampsia.